KEGIATAN PENGABDIAN MASYARAKAT DENGAN INTERVENSI BESTI (BISKUIT, TELUR, SUSU) UNTUK PERBAIKAN STATUS GIZI BALITA DI KELURAHAN RAGUNAN JAKARTA SELATAN - Rini Kundaryanti; Astiara Wijayanti; Elsa Monica Shinta Ayu Fransisca; Dzihni Atifah; Karisma Septiyanih Wulandari; Taqiyya Hasya Tsabitha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Malnutrition among toddlers remains a public health issue that affects children's growth and development. One of the contributing factors is low intake of animal protein and parents' lack of knowledge about balanced nutrition. This community service program aims to improve the knowledge of mothers of toddlers and provide supplementary food interventions as an effort to improve the nutritional status of toddlers. The activity was carried out on December 30, 2025, in RT 08 RW 07, Ragunan Village, Pasar Minggu Subdistrict, South Jakarta, targeting malnourished toddlers. The methods used included toddler nutrition counseling and the provision of BESTI (Biscuits, Eggs, Milk) supplementary food innovations based on animal protein. The results of the activity showed an increase in the knowledge and understanding of mothers of toddlers regarding balanced nutrition. The BESTI intervention was considered practical, economical, and well received by toddlers and families. This activity shows that a combination of nutrition education and the provision of simple family-based supplementary foods has the potential to be a promotive and preventive strategy in addressing malnutrition among toddlers in the community.